Visible‐Light Photocatalytic Reduction of Sulfonium Salts as a Source of Aryl Radicals. Issue 8 (17th May 2013) - Donck, Simon; Baroudi, Abdulkader; Fensterbank, Louis; Goddard, Jean‐Philippe; Ollivier, Cyril
Abstract: Triarylsulfonium salts are prompted to undergo efficient homolytic reduction by single electron transfer under mild photocatalytic conditions. The liberated aryl radical can then participate in carbon‐carbon bond formation processes with allyl sulfones and activated olefins. Triarylsulfonium salts emerge as a valuable and alternative source of aryl radicals for synthesis. Abstract :